Identification and Characterization of the RNA Modifying Factors PUS7 and WTAP as Key Components for the Control of Tumor Biological Processes in Renal Cell Carcinomas - Tim Hohmann; Urszula Hohmann; Faramarz Dehghani; Olaf Grisk; Simon Jasinski-Bergner (Current Issues in Molecular Biology)
Current research discusses the putative importance of RNA modification in tumor diseases. These RNA modifications include predominantly pseudouridinylation, ortho-methylations on the ribose residues, as well as methylations on the organic bases. Such chemical modifications directly influence fundamental properties such as transcript stability, alternative splicing, and translation efficiency, all of which are basic requirements for (tumor) cell proliferation, cell metabolism, cell migration, apoptosis resistance, etc. In this comparative study, the two RNA-modifying factors, pseudouridine synthase 7 (PUS7, RNA pseudouridinylation) and WT1-associated protein (WTAP, m6A RNA methylation), were identified using data from human renal cell carcinoma (RCC) tumors. PUS7 and WTAP showed a statistically significant correlation with relevant proliferation and prognosis markers such as CXCR4, TP53, PTEN, and NRAS, as well as with the two tumor immune checkpoints HLA-G and LGALS9 and were directly associated with a statistically significant effect on overall survival. Furthermore, comparative analyses also identified further putative target mRNAs of importance for tumor biology of PUS7 and WTAP. In particular, components with direct relevance for mitosis, the cell cycle, and cell division, as well as the WNT pathway, were identified.